The Effect of Ethanol Extract of Avocado Leaf (Persea Americana Mill.) on Reduction of Gastric Acid in Aspirin Induced Rats - Simbolon, Rohana Oktofariday; Dalimunthe, Aminah; Bangun, Hakim (Newinera Publisher, 2024)
One of the most prevalent dangerous illnesses is arthritis. The pathophysiology of gastritis is an imbalance of aggressive and protective factors. Nonsteroidal anti-inflammatory drugs are known as aggressive agents for the development of gastritis. Gastritis can be managed using avocado leaves. Finding out how an avocado leaf ethanol extract changed the amount of stomach acid in aspirin-treated rats was the aim of the investigation. Secondary metabolite content and characterisation were examined in the avocado leaf ethanol extract. Gastric acid reduction was performed by examining gastric acid concentration, number of ulcers, ulcer index, and pH in aspirin-induced rats. Ethanol extract of avocado leaves contains alkaloids, flavonoids, saponins, steroids, tannins and glycosides. Characterization obtained moisture content of 12.60%, total ash content of 1.34% and acid insoluble ash content of 0.17%. Acid concentration in the administration of avocado leaf ethanol extract 400 mg/KgBW is 16.00 ± 2.65 significantly different from the negative control 27.67 ± 2.52. The number of ulcers on the administration of avocado leaf ethanol extract 400 mg/KgBW 1.67 ± 2.08 is significantly different from the negative control 5.33 ± 0.58. When avocado leaf ethanol extract 400 mg/ kgBW is administered, the ulcer index (0.003 ± 0.005) differs significantly from the negative control (0.014 ± 0.013). pH in the administration of avocado leaf ethanol extract 400 mg / kgBW 5.53 ± 0.57 is significantly different from the negative control 2.57 ± 0.12. The ethanol extract of avocado leaf 400 mg/kgBW has a reducing gastric acid effect.